Research and Extension Gaps in Commercial Vegetable Farming in Eastern Palakkad - Kamalakkannan K (Department of Agricultural Extension, College of Horticulture, 2003)
The present study entitled "Research and extension gaps In commercial . vegetable farming in eastern Palakkad" was conducted with the prime objective of identifying and prioritizing the problems/constraints in commercial vegetable farming followed by exploration of the availability of technological interventions with the research system to tackle them and further to study the research - extension gaps associated with it. Eighty randomly selected vegetable growers representing 20 harithasangams of Nemmara block were the respondents for the study. The status of commercial vegetable farming in the study area and problems/constraints experienced in commercial cultivation and marketing of the important vegetables were elicited using PRA, farmers-extensionists-scientists interaction, field investigations and personal interviews. The lists of identified problems were discussed by a multidisciplinary research team to explore the availability of technological interventions with KAU research system and the gaps thereon in vegetable research. Bitter gourd showed a wider research gap while bhindi was reported to have no research gap with respect to the number of specific problems left unaddressed in the POP recommendations of the university. The identified problems/constraints in commercial vegetable farming were ~ ranked based on their severity as perceived by the farmers. The appropriate technological interventions recommended by the multi disciplinary research team based on extensive review of POP were listed and included in the interview schedule to study the knowledge and adoption levels of these recommended vegetable production technologies. It was found that majority of the commercial vegetable growers had medium level of knowledge and adoption with respect to the recommended package of practices of KAU on vegetable cultivation.